LIF instrument development, in situ measurement at South Pole and 1D air-snowpack modeling of atmospheric nitrous acid (HONO) - Liao, Wei (Georgia Institute of Technology, 2008)
Atmospheric nitrous acid (HONO) is a significant and sometimes dominant OH source at polar region. An improved method of detecting HONO is developed using photo-fragmentation and laser-induced fluorescence (LIF). The detection limit of this method is 2-3 pptv for ten-minute integration time with 35% uncertainty. The abundance of laser-induced fluorescence (LIF) HONO measurements during ANTCI (Antarctic troposphere chemistry investigation) 2003 exceeds the pure gas phase model predictions by a factor of 1.92±0.67, which implies snow emission of HONO. A 1D air-snowpack model of HONO was developed and constrained by observed chemistry and meteology data. The 1D model includes pure gas phase chemical mechanisms, molecular diffusion and mechanical dispersion, windpumping in snow, gas phase to quasi-liquid layer phase HONO transfer and quasi-liquid layer nitrate photolysis. Based on the air-snowpack model, snow emission of HONO is highly likely and will be transported to place of the measurements. The pH, thickness of quasi liquid layer and contineous nitrite measurement are key factors to calibrate and validate the air snowpack model. Ph.D.